PENYULUHAN TENTANG MENCUCI TANGAN DENGAN SABUN DI SDN 108 PEKANBARU - Devi Purnamasari; Aulia Annisa (Awal Bros Journal of Community Development, 2020)
The behavior of washing hands using soap that is not true is still high in children, so that it needs to increase their knowledge and awareness of the importance of washing hands using soap and it can be applied in everyday life. The method of implementation is to provide direction to students about the importance of washing hands with soap and provide leaflets on the steps for washing hands. Elementary school children understand the steps of a healthy lifestyle, one of which is washing their hands with soap